Pulmonary Mucormycosis: A Case Report of a Rare Infection with Potential Diagnostic Problems - Salwa O. Mekki; Amal A. Hassan; Afnan Falemban; Nashwa Alkotani; Salem M. Alsharif; Ahmed Haron; Basim Felemban; Mohammad S. Iqbal; Aisha Tabassum (Case Reports in Pathology)
Pulmonary mucormycosis is a relatively rare pulmonary fungal disease, which is difficult to diagnose early and lacks effective treatment. It is seen in patients with hematological malignancies, diabetes mellitus, and immunocompromised states. The diagnosis depends primarily on the detection of fungi in lung tissue. Here, we present a case of a 52-year-old male who has type 2 diabetes mellitus and a past history of treated pulmonary tuberculosis. Clinical diagnosis is difficult in pulmonary mucormycosis, and early diagnosis is needed for this life-threatening infection. Histopathological examination of a resected cavity confirmed the diagnosis of pulmonary mucormycosis. This report highlights the difficulty of diagnosis and the importance of histological examination in detecting mucormycosis which will help for early management.